Kedudukan hukum pembeli apartemen yang hanya memiliki ppjb terhadap eksekusi hak tanggungan atas hak atas tanah milik developer - Lintang Lasmita Sari; Novena Kristina Sari; Deddy Siswanto (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2026)
The rapid growth of vertical property development in Indonesia has given rise to widespread pre-project selling practices, in which the Sale and Purchase Binding Agreement (Perjanjian Pengikatan Jual Beli/PPJB) serves as the primary instrument between developers and buyers prior to the issuance of a Deed of Sale and Purchase. From a legal standpoint, buyers holding only a PPJB possess merely personal rights (persoonlijk recht) that cannot be asserted against third parties, placing them in the position of concurrent creditors under Articles 1131 and 1132 of the Civil Code. This vulnerability becomes critical when developers encumber project land with mortgage rights (Hak Tanggungan) as collateral and subsequently default, exposing buyers to the risk of asset execution. This study employs a normative juridical method through statutory and conceptual approaches to examine the legal standing of PPJB holders, available legal protections, and accessible legal remedies. The findings reveal that although Supreme Court Circular Letter Number 4 of 2016 provides some protection for good-faith buyers, the executorial authority of mortgage holders as preferential creditors remains normatively superior. Legal remedies such as third-party opposition (derden verzet), actio pauliana, and consumer dispute resolution have proven insufficient to fully restore buyers' rights. Comprehensive regulatory reform, including mandatory escrow account mechanisms and stricter oversight of pre-project selling, is urgently needed.